2020
DOI: 10.1080/01919512.2020.1842998
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Inactivation by Ozonated Water: A Preliminary Alternative for Environmental Disinfection

Abstract: The rapid spread of SARS-CoV-2 caused a global pandemic. Due to the lack of treatment and vaccines, safety strategies must be found to stop the virus dissemination. The objective of this study was to evaluate the virucidal activity of ozonated water, a powerful oxidizing agent, against SARS-CoV-2. A special faucet was the source of ozonated water at a low concentration (0.2-0.8 ppm). At this concentration, tests with SARS-Cov-2 in Vero CCL81 lineage showed two log 10 reduction in virus infectivity upon 1 min e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 12 publications
1
26
0
1
Order By: Relevance
“…to inactivate SARS-CoV-2 on different materials, most of them require long duration and energy consumption and even present side effects on the human body and environment. 33–36 Thus, a more effective, economical, without side effects, and green mean to avoid environmental transmission of SARS-CoV-2 is urgent.…”
Section: Introductionmentioning
confidence: 99%
“…to inactivate SARS-CoV-2 on different materials, most of them require long duration and energy consumption and even present side effects on the human body and environment. 33–36 Thus, a more effective, economical, without side effects, and green mean to avoid environmental transmission of SARS-CoV-2 is urgent.…”
Section: Introductionmentioning
confidence: 99%
“…OW has recently been shown to reduce the infectivity of SARS-CoV-2 following exposure of the virus to low concentrations of OW for 1 min (Martins et al, 2021 ). In addition, 10 ppm OW, which is a high ozone concentration for OW, rapidly inactivates SARS-CoV-2 (Inagaki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, OW is known as a powerful inactivating agent against bacteria, fungi, protozoa, and viruses (Kim et al, 1999 ), and has been suggested to exert antimicrobial effects in running water (Nakamura et al, 2018 ). More recently, low concentrations of OW were shown to reduce viral infectivity upon exposure to SARS-CoV-2 for 1 min (Martins et al, 2021 ). In addition, it was reported that high ozone concentrations in OW rapidly inactivated SARS-CoV-2 (Inagaki et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the amount of virus produced, a tenfold serial dilution of the plasmid was prepared in the range from 10 6 to 1 plasmid copy. The coefficient of determination ( R 2 ) for the plasmid standard curve was 0.999, with efficiency above 91% reached using any set of primers/probe 51 .…”
Section: Models and Methodsmentioning
confidence: 97%